2017
DOI: 10.1016/j.envexpbot.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

A spring rainfall pulse causes greater in situ photosynthetic upregulation for Bromus tectorum compared to co-occurring native herbaceous species

Abstract: A B S T R A C TThe invasive grass Bromus tectorum fuels fires, displaces native species, and reduces wildlife habitat on sagebrush steppe throughout the western United States. Recently, it has spread from the Great Basin Desert into higher elevations of the eastern Sierra Nevada, where it coexists with natives but has not yet altered fire regimes. We evaluated effects of a springtime water pulse (+10 mm) in a drought year on photosynthesis for B. tectorum and co-occurring shallow-rooted native perennials Achna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…In Northeastern California, Coates et al (2016) noted that increased precipitation may, in fact, result in less sagebrush, as fine-fuel densities (i.e., cheatgrass) increase with more precipitation, resulting in larger burned areas. Indeed, Wade and Loik (2017) found that cheatgrass is able to take advantage of a pulse of spring precipitation, as measured through carbon assimilation, compared to other native plant species.…”
Section: Fire Processes and Disturbancementioning
confidence: 99%
“…In Northeastern California, Coates et al (2016) noted that increased precipitation may, in fact, result in less sagebrush, as fine-fuel densities (i.e., cheatgrass) increase with more precipitation, resulting in larger burned areas. Indeed, Wade and Loik (2017) found that cheatgrass is able to take advantage of a pulse of spring precipitation, as measured through carbon assimilation, compared to other native plant species.…”
Section: Fire Processes and Disturbancementioning
confidence: 99%